Identifikasi Karakteristik Kimiawi dan Daya Simpan Kefir Susu Jagung (Zea mays L. Saccharata) - Lestari, Yanesti Nuravianda; Amin, Nur; Ananda, Duyung; Rengganis, Nimas Ayu (Universitas Muhammadiyah Semarang, 2021)
Kefir is a food-based on pasteurized milk fermented using lactic acid bacteria, aceticacid bacteria, and yeast. The study aims to analyze proximate levels (carbohydrates, proteins,and fats) and identify the characteristics of sensory changes during storage. This true experimental study uses a complete randomized design with 1 factor. Thecomposition of corn milk kefir consists of 3 levels (K1=corn milk: skimmed milk 100:0;K2=corn milk: skimmed milk 75:25; K3=corn milk: skimmed milk 50:50). Data analysisusing One Way Anova showed that carbohydrate content (10.31 + 1,426), fat (0.18 + 0.018),and protein (1.83 + 0.973) significantly different (p=0.0001). The 35 days of storage in the refrigerator (2-8C) results in a change in kefir colorbecoming more faded. The kefir texture before storage is different for each kefir compositionand becomes more viscous at the end of the storage period. The sour aroma of kefir willincrease during kefir storage. It can be concluded that protein and fat levels increase alongwith an increase in the amount of skimmed milk addition, while carbohydrate levels decreaseat the addition of the most skimmed milk (K3).Keywords: kefir, proximate, sensory characteristics, shelf-life, skimmed milko